Edna O'Brien and the art of fiction - O'Connor, Maureen, 1960- (Contemporary Irish writers (Lewisburg, Pa.), 2022)
"Since the appearance of her first novel, The Country Girls, in 1960-a book that undermined the nation's ideal of innocent and pious Irish girlhood--Edna O'Brien has provoked controversy in her native Ireland and abroad. Indeed, several of her early novels were condemned by church authorities and banned by the Irish government for their frank portrayals of sexual matters and the inner lives of women. Now an internationally acclaimed writer, O'Brien must be critically reassessed for a twenty-first century audience. Edna O'Brien and the Art of Fiction provides an urgent retrospective consideration of one of the English-speaking world's best-selling and most prolific contemporary authors. Drawing on O'Brien's fiction as well as archival material, and applying new theoretical approaches-including ecocritical and feminist new materialist readings-this study considers the pioneering and enduring ways O'Brien represents women's experience, family relationships, the natural world, sex, creativity, and death, and her work's long anticipation of contemporary movements such as #metoo"--